2020
DOI: 10.1021/acssuschemeng.9b07738
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Formamidinium-Based Planar Perovskite Solar Cells Fabricated Through a CaI2–PbI2 Precursor

Abstract: The performance of perovskite solar cells (PSCs) is sensitive to the quality of perovskite films. Sequential deposition enabling the controlled growth of film is promising to obtain high-quality perovskite films. However, it is challenging to fabricate formamidinium-based planar PSCs via sequential deposition, mainly due to the small penetration depth of the large size formamidinium cation into a compact PbI2 film during perovskite formation. Here, CaI2 is introduced into PbI2 precursor solution, which brings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Consequently, the optimized perovskite film can decrease the energy level barrier at the interface with SnO 2 ; this can facilitate excellent electron transport, reduce energy loss in the process of charge separation, and contribute to the enhancement of J sc and V oc . [ 35,36 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the optimized perovskite film can decrease the energy level barrier at the interface with SnO 2 ; this can facilitate excellent electron transport, reduce energy loss in the process of charge separation, and contribute to the enhancement of J sc and V oc . [ 35,36 ]…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the optimized perovskite film can decrease the energy level barrier at the interface with SnO 2 ; this can facilitate excellent electron transport, reduce energy loss in the process of charge separation, and contribute to the enhancement of J sc and V oc . [35,36] The UV-vis absorption spectra of the perovskite films under different masses BaCl 2 additive were shown in Figure 4a. By spin-coating the perovskite precursor solution on the conductive substrate, the UV-vis spectra of the films were tested after heating to examine the optical band gap of the perovskite with an initial wavelength of 900 nm.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it has been pointed out that more PbI 2 is beneficial to the improvement of device performance. [ 42,43 ] The influence of the 10 mg KC‐SnO 2 on optical properties of perovskite thin films was further investigated by recording the UV–vis absorption spectra, as shown in Figure 5f. It has been shown that the absorption edge for the perovskite thin films based on reference SnO 2 and 10 mg KC‐SnO 2 ETLs appeared about 790 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Several structures including surface texturing [4][5][6], anti-reflection coatings [7,8], photonic crystals [9], nanogratings [10,11], and metallic nanoparticles [12][13] have been presented to enhance the absorption of plasmonic solar cells. Solar cells are generally classified into four generations [14][15][16][17][18]. By various Received:20 May, 2020, Accepted: 31 July , 2020 techniques of nanostructures, light can be concentrated in a thin absorber layer through scattering, enhanced near-field, or surface plasmon polariton phenomenon [1,2].…”
Section: Introductionmentioning
confidence: 99%